Health promotion interventions in social economy companies in Flanders (Belgium). (December 2015) - Hublet, Anne; Maes, Lea; Mommen, Jasmine; Deforche, Benedicte; De Bourdeaudhuij, Ilse
Abstract Background Disadvantaged groups are often not reached by mainstream health promotion interventions. Implementing health promotion (HP) interventions in social economy companies, can be an opportunity to reach those people. The implementation of these interventions in social economy companies was studied. Factors that could be related to the implementation of HP and being supportive towards implementation in the future, were investigated. Methods An online, quantitative survey was sent to all 148 sheltered and social workshops in Flanders. In the questionnaire, the status of HP interventions and characteristics of the workshop were explored. Personal factors (such as attitudes towards HP, behavioural control, social norms and moral responsibility) were asked to the person responsible for implementation of HP interventions. Univariate and multivariate logistic regressions were performed. Results Respondents of 88 workshops completed the questionnaire. Almost 60 % of the workshops implemented environmental or policy interventions. Having a positive attitude towards HP, being more morally responsible, and having the subjective norm that employees are positive towards health promotion at work, were related to being more supportive towards the implementation of HP in the univariate analyses. Only attitude stayed significantly related to being more supportive towards the implementation of HP in the multivariate analyses. Conclusions Sheltered and social workshops are open to HP interventions, but more can be done to optimize the implementation. To persuade persons responsible for the implementation of HP to invest more in HP, changing attitudes concerning the benefits of health promotion for the employee and the company, is an important strategy.